Exploring the drivers and barriers to the adoption of plant-based meat alternatives: a study based in the United Arab Emirates - Tausif Mulla; Sufia Munir; Vivek Mohan; Farah Zahidi (Cogent Business & Management)
This study examines consumer adoption of plant-based meat alternatives (PBMA) in the United Arab Emirates, a culturally diverse nation with expatriates from over 175 countries. Using qualitative semi-structured interviews and thematic analysis through NVivo Pro 12, the research identifies key drivers and barriers influencing PBMA acceptance in this unique multicultural context. The findings reveal that environmental consciousness, health benefits, ethical considerations, and improved accessibility serve as primary adoption drivers. However, significant barriers include consumer unfamiliarity, perceptions of over-processing, health concerns, and skepticism about PBMA as legitimate meat substitutes. Five influential themes emerged: attitudes, awareness, peer influence, environmental sustainability, and nutritional values. Cultural factors proved particularly significant in the UAE’s diverse demographic landscape, with social norms, family traditions, and cultural preferences substantially impacting food choices. The study aligns with the Theory of Planned Behavior, highlighting attitudes and awareness as central determinants of consumer behavior. These findings address a research gap in understanding PBMA adoption within the UAE and broader Middle East region. The research provides valuable insights for policymakers, marketers, and industry stakeholders, emphasizing the need to address identified barriers while promoting PBMA awareness in culturally diverse markets. The study contributes to understanding how cultural context shapes consumer behavior toward sustainable food alternatives.